2016
DOI: 10.1016/j.bios.2016.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy combined with human pluripotent stem cell derived cardiomyocytes for biomechanical sensing

Abstract: Cardiomyocyte contraction and relaxation are important parameters of cardiac function altered in many heart pathologies. Biosensing of these parameters represents an important tool in drug development and disease modeling. Human embryonic stem cells and especially patient specific induced pluripotent stem cell-derived cardiomyocytes are well established as cardiac disease model.. Here, a live stem cell derived embryoid body (EB) based cardiac cell syncytium served as a biorecognition element coupled to the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 45 publications
6
46
0
Order By: Relevance
“…In this condition, no movement of the DM1 BB could be seen by AFM measurements and even through conventional microscopy. This behavior was observed only in the DM1 samples and is consistent with a loss of synchronicity between the different contraction centers …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In this condition, no movement of the DM1 BB could be seen by AFM measurements and even through conventional microscopy. This behavior was observed only in the DM1 samples and is consistent with a loss of synchronicity between the different contraction centers …”
Section: Resultssupporting
confidence: 79%
“…Due to its peculiarities, AFM is one of the few techniques that can directly access beating rate and intensity, from an entire BB under physiological conditions and under the action of several drugs. For instance, a recent work from Rotrekl's group have shown how AFM can monitor WT BBs under mechanical stress conditions, while at the same time recording the cellular calcium and electrophysiology response.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the complications mentioned in the previous chapter, our group has successfully developed reliable uniformly sized EB models, containing hPSC‐CMs . These cellular constructs of cardiac syncytium were coupled to an atomic force microscopy (AFM) force sensor to perform a high‐fidelity contraction pattern as an hPSC‐CM–based biosensor . The high consistency in the cluster of cells and its constant size among different cell lines allow a comparable and stable beating pattern.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…The ability of AFM to evaluate the bending of the cantilever probe with extremely high precision allows this device to be used as a mechanical nanosensor or as a micromechanical transducer for the construction of complex nanobiosensors, such as in the FluidFM modification by Ossola et al Atomic force microscopy as a base for construction of a biosensor device, when combined with bio‐objects as a recognition part, was used as a mechanical sensor for cell penetration by nanoneedles, in cell‐based biosensing of drug effects and in the study of grow factor effects . The use of AFM to study mechanobiological properties was demonstrated in single cells and clusters . Lieu and coworkers have used AFM in synergy with Ca 2 + imaging to prove that hESC‐CMs lack T‐tubule structures, fundamental in adult CMs for the proper Ca 2 + ‐induced Ca 2 + release mechanism .…”
Section: Methods Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation